Consensus Building during Nest-Site Selection in Honey Bee Swarms: The Expiration of Dissent - Seeley, Thomas D. (Behavioral ecology and sociobiology, 2003)
This study addresses a question that lies at the heart of understanding how the scouts in a honey bee swarm achieve unanimity in their dances, and so reach agreement in their choice of a future nest site: what causes the scouts that perform dances for the non-chosen sites to stop dancing for these sites? One possibility is that a scout stops dancing for a non-chosen site only after she follows a lively dance for another site, such as the site that is ultimately chosen. This hypothesis is contradicted by the finding that 23 out of 27 scouts (in 6 swarms) that danced initially for a non-chosen site stopped their dancing before they followed a dance for another site. Evidently, a scout that supports initially one of the non-chosen sites is likely to withdraw her support for this site even before she learns about another site. What causes her to do so? Close examination of the behavior of scouts revealed that they reduce the strength of their dancing (waggle runs/return to the swarm) for a given site over consecutive returns to the swarm. On average, the pattern of this reduction in dancing is strikingly linear, which suggests that it arises from an internal, neurophysiological process that automatically drives down a scout's motivation to dance for a site. Other results suggest that scouts from inferior sites start their dancing less strongly, and so cease their dancing more rapidly, than do scouts from superior sites. If so, then during the consensus-building process of the scouts, it is the support (the dancing) for inferior sites that is most likely to die out while it is the support for a superior site that is most likely to prevail.